Drought‐Proofing Barley (Hordeum vulgare): The Effects of Stay Green on Starch and Amylose Structure. Issue 5 (22nd June 2017) - Gous, Peter W.; Warren, Frederick; Gilbert, Robert; Fox, Glen P.
Abstract : The identification of the plant physiological trait called stay green (SG) was first identified in sorghum ( Sorghum bicolor L. Moench), followed by other cereals, including barley. The effects of this drought tolerance trait on starch biosynthesis, structure, and properties have not been extensively investigated. Using size‐exclusion chromatography, the impact of SG expression on starch molecular structure in barley ( Hordeum vulgare L.) under heat‐ and water‐stress conditions was examined. Differences were found in total starch and amylose contents within and between the treatments. The chain‐length distribution of the amylose in a heat‐stressed doubled haploid, ND24260 × Flagship population expressing SG showed significant differences ( P < 0.05), whereas no such differences were observed in the water‐stressed samples. However, significant differences ( P < 0.05) in protein content were observed corresponding to SG expression, with higher levels of SG expression having higher protein content. These differences in composition and starch structure could influence functional properties. Understanding physiological responses in plants to abiotic stress and its impact on grain quality and starch biosynthesis may allow for the future manipulation of plants to improve drought tolerance, while maintaining desirable grain quality and yield potential.